Volatilomik Gelatin Ikan dan Babi dengan HS-SPME GC-MS untuk Autentikasi Halal - Hanifati, Fadiah Nur; Kusnandar, Feri; Darmawan, Noviyan; Pranata, Agy Wirabudi; Yuliana , Nancy Dewi (Jurnal Teknologi dan Industri Pangan, 2026)
Gelatin, derived from animal tissues, is a widely used ingredient in the food industry. Fish gelatin has gained attention as a halal alternative due to its abundance, favorable functional properties, and versatility in food applications. However, tracing the origin of gelatin remains challenging, highlighting the need for reliable authentication methods. Conventional analytical techniques are often limited by long analysis times, low specificity, inability to detect source-specific markers, high costs, and the requirement for sophisticated instruments. This study investigated the volatile compound profiles of commercial gelatin from various fish species (pangasius, tilapia skin, tuna skin, and cod) and compared them with commercial pork gelatin by using Headspace Solid-Phase Microextraction coupled with Gas Chromatography-Mass Spectrometry (HS-SPME GC-MS) combined with multivariate data analysis. The HS-SPME GC-MS approach effectively classified gelatin samples based on their volatile profiles. Partial least squares-discriminant analysis (PLS-DA) identified five key discriminant volatiles for pork gelatin (decane, boronic acid, ethyl-, bis(2,2-dimethylpropyl) ester, m-anisoyl amide, N-(2-phenylethyl)-N-decyl, 1-pentadecene, and 2-tetradecanone) and four for fish gelatin (hexadecane, 1,2-oxathiane, 6-dodecyl, 2,2-dioxide, n-tridecan-1-ol, and 9-nonadecene), with decane and hexadecane identified as the most influential markers for pork and fish gelatin, respectively.